Estimation of fluid force acting on the hand and joint torque of upper extremity in the breaststroke swimming - Suito, H.; Okamoto, A.; Takahashi, S.; Sakurai, S.; Sano, S.; Nunome, H.; Ikegami, Y. (Japanese Journal of Sciences in Swimming and Water Exercise, 2006)
The purpose of this study was to estimate the propulsive force of the hand, and the joint torque generated in the arm pull during the breaststroke swimming. Subject was one Japanese male elite swimmer in breaststroke. The swimming motion in breaststroke of the swimmer was recorded by using four synchronized video cameras. Ten landmarks on the right upper body were digitized at 60 Hz and their three-dimensional coordinates were obtained using a DLT method. The fluid force acting on the hand was calculated using the drag and lift coefficients by Schleihauf 12). The arm was modeled as a three-links kinetic chain composed of the upper arm, forearm and hand, and angular velocities and joint torques were computed. Lift force was dominant rather than drag, which were generated by the arm pull motion. Large torque was observed in wrist palmar flexion, elbow flexion and shoulder horizontal abduction and horizontal adduction.